2016
DOI: 10.1002/humu.23042
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum ofMYO15Aand the Molecular Mechanisms of DFNB3 Human Deafness

Abstract: Deafness in humans is a common neurosensory disorder and is genetically heterogeneous. Across diverse ethnic groups, mutations of MYO15A at the DFNB3 locus appear to be the third or fourth most common cause of autosomal recessive, nonsyndromic deafness. In 49 of the 67 exons of MYO15A, there are currently 192 recessive mutations identified, including 14 novel mutations reported here. These mutations are distributed uniformly across MYO15A with one enigmatic exception; the alternatively spliced giant exon 2, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 105 publications
(167 reference statements)
4
70
0
Order By: Relevance
“…(Arg297Cys) in DHX38 (MIM: 605584) in which two other amino acid substitutions have been reported in individuals with autosomal recessively inherited early-onset retinitis pigmentosa (MIM: 268000) [52,53] and c.5083C>A/p. (Pro1695Thr) in MYO15A (MIM: 602666) in which biallelic mutations cause autosomal-recessive, nonsyndromic deafness (DFNB3, MIM: 600316) [54,55]. The MYO15A change c.5083C>A is no known disease-associated allele.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…(Arg297Cys) in DHX38 (MIM: 605584) in which two other amino acid substitutions have been reported in individuals with autosomal recessively inherited early-onset retinitis pigmentosa (MIM: 268000) [52,53] and c.5083C>A/p. (Pro1695Thr) in MYO15A (MIM: 602666) in which biallelic mutations cause autosomal-recessive, nonsyndromic deafness (DFNB3, MIM: 600316) [54,55]. The MYO15A change c.5083C>A is no known disease-associated allele.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…[ 10 12 ] At present, previous genetic screening studies have shown that a few genes mutations are known to cause hereditary hearing loss or deafness, such as GJB2 (gap junction beta-2 protein; OMIM: 121011), GJB3 (gap junction beta-2 protein; OMIM: 603324), SLC26A4 (solute carrier family 26 member 4; OMIM: 605646), and the mitochondrial gene MT-RNR1 (mitochondrially encoded 12S RNA; OMIM: 561000). [ 9 , 13 24 ] Knowledge of the gene mutation can help to identify hearing impairment at birth, and the educational programs for auditory stimulation and sufficient language exposure in early childhood can begin immediately. Furthermore, it can also provide warning to avoid taking certain types of aminoglycosides antibiotics, such as streptomycin, gentamicin, and tobramycin, which are known to cause deafness in children carrying certain mitochondrial gene mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Myosin XVA is an unconventional myosin encoded by the human MYO15A gene and consists of 3530 amino acids. It is expressed at the tips of hair cell stereocilia in the inner cochlear region [7][8][9]. Three evolutionally conserved regions (head, neck, and tail) are present in this protein.…”
Section: Discussionmentioning
confidence: 99%